Catalytic Biomineralization of Fluorescent Calcite by the Thermophilic Bacterium Geobacillus thermoglucosidasius - Yoshida, Naoto (American Society for Microbiology (ASM), 2010)
The thermophilic Geobacillus bacterium catalyzed the formation of 100-μm hexagonal crystals at 60°C in a hydrogel containing sodium acetate, calcium chloride, and magnesium sulfate. Under fluorescence microscopy, crystals fluoresced upon excitation at 365 ± 5, 480 ± 20, or 545 ± 15 nm. X-ray diffraction indicated that the crystals were magnesium-calcite in calcite-type calcium carbonate.